INDIGENOUS ART OF WEST AFRICA IN WOOD (Global Journal of Human-Social Science, 2011)
Art as it has been defined severally it has many definitions of its own but in the context of this paper Art will be defined as a means of self-expression with the medium which one is familiar with Wood is one of the very important means of artistic representation which the Africans have used and are still making use of in bringing forth and producing artistic works aimed at documenting peoples way of life as well as their religious and socio- cultural values African wood sculptures are not older than two centuries old because of the susceptible nature of wood to the destructive effect of termites and climate Wood is the Africans most favourite material or medium for sculpture Hard termite-resistant woods are preferred for sculpture Iroko wood chlorophora excelsa Mahogany and Ebony varieties which are suitable for extremely delicate carving For the large masks lighter woods are chosen which do not weigh so heavy when worn The African traditional artist or carver doesn t just go to the forest to fell trees indiscriminately If there is any particular tree they are interested in in the forest they carry out some sacrifices to find out from the tree itself if it would like to be fell or not And if any particular tree is to be felled they carry out some sacrifices before they touch the tree at all I would like to make the following West African countries as my area of focus in this paper with particular references to their masks stools and architectural designs These countries are Nigeria Ghana Sierra-Leone and Mali